2023
DOI: 10.7554/elife.83694
|View full text |Cite
|
Sign up to set email alerts
|

Study of efficacy and longevity of immune response to third and fourth doses of COVID-19 vaccines in patients with cancer: A single arm clinical trial

Abstract: Background: Cancer patients show increased morbidity with COVID-19 and need effective immunization strategies. Many healthcare regulatory agencies recommend administering 'booster' doses of COVID-19 vaccines beyond the standard 2-dose series, for this group of patients. Therefore, studying the efficacy of these additional vaccine doses against SARS-CoV-2 and variants of concern is of utmost importance in this immunocompromised patient population.Methods: We conducted a prospective single arm clinical trial enr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Since at that time 32% of the enrolled patients had already developed COVID-19 breakthrough infections, these pharmacological interventions cannot be considered applicable to the general study population. Evidence that additional booster doses may increase COVID-19 protection for cancer patients, even those who do not respond to the initial vaccine series, introduces potential confouders that we could not foresee at the beginning of this research [36].…”
Section: Discussionmentioning
confidence: 98%
“…Since at that time 32% of the enrolled patients had already developed COVID-19 breakthrough infections, these pharmacological interventions cannot be considered applicable to the general study population. Evidence that additional booster doses may increase COVID-19 protection for cancer patients, even those who do not respond to the initial vaccine series, introduces potential confouders that we could not foresee at the beginning of this research [36].…”
Section: Discussionmentioning
confidence: 98%
“…The fact that individuals with SARS‐CoV‐2 negative serology have worse outcomes than seropositive patients can be quite intuitive. In fact, SARS‐CoV‐2 serology can be considered an appropriate surrogate marker of patient immune response, being demonstrated that the higher the titer of the anti‐S antibody, the higher the likelihood of neutralization in neutralization assays [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study had a few limitations, the first being that we did not determine immunogenicity against different SARS-CoV-2 variants, particularly the Omicron variant, against which existing data show reduced vaccine efficacy [ 25 , 31 , 32 ]. The number of patients in each subcategory for analysis was lower in some therapies than others, limiting our ability to make conclusions for certain patient subsets.…”
Section: Discussionmentioning
confidence: 99%